2015
DOI: 10.1371/journal.pone.0117939
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Optic Nerve Sheath Diameter Threshold for the Identification of Elevated Opening Pressure on Lumbar Puncture in a Chinese Population

Abstract: Ultrasonography of the optic nerve sheath diameter (ONSD) is a non-invasive and rapid method that might be helpful in the identification of increased intracranial pressure (ICP). The use of an ONSD greater than 5 mm on ultrasound as an indicator of increased ICP in a Caucasian population has been studied. However, the cut-off point of this predictor in Chinese patients has not been established. Thus, we conducted this study to identify the ONSD criterion for the detection of elevated opening pressure on lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 35 publications
2
67
2
3
Order By: Relevance
“…In addition, the patients in that study were from western countries, and the ONSD varied among different races. Wang et al found that among the Chinese population, the predicted cut-off value of ONSD that means intracranial pressure higher than 20 cmH2O was lower than that in Caucasians [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patients in that study were from western countries, and the ONSD varied among different races. Wang et al found that among the Chinese population, the predicted cut-off value of ONSD that means intracranial pressure higher than 20 cmH2O was lower than that in Caucasians [27].…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been used to detect elevated ICP with sensitivity and specificity ranging from 84 to 98% and 42 to 92%, respectively (►Table 1). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The values can be compared with the results of two different meta-analyses from 2011 and 2015 that demonstrated the ability of ONSD ultrasonography to yield average sensitivity and specificity ranging from 90 to 95% and 85 to 92%, respectively. 29,30 A more recent meta-analysis found sensitivity and specificity to range from 88 to 95% and 74 to 96%, respectively.…”
Section: Noninvasive Diagnostics and Monitoring Noninvasive Measuremementioning
confidence: 99%
“…There have also been a number of studies that compared ocular ultrasound-derived ONSD with ICP measured by LP opening pressure or invasive monitoring. In the adult population, the literature shows evidence for cutoff values ranging from 4.1 to 5.7 mm, which are associated with 74.1 to 100 % sensitivity and 74 to 100 % specificity [35,36]. Interestingly, [37].…”
Section: Ocular Ultrasoundmentioning
confidence: 99%